Electronic structures and reactivities of derivatives of 1,4-dihydropyridines. 1. 1-methyl-3-carbamidopyridinyl radical and 1-methyl-3-carbamidopyridinium cation - Nesterenko, A.; Buryak, Nadezhda; Polumbryk, Oleg; Yasnikov, A. (My University, 1987)
The physicochemical properties and electronic and three-dimensional structures of the products of transformations of 1-methyl-1,4-dihydronicotinamide were calculated within the MINDO/3 approximation. The problems associated with their reactivities in reactions involving electron and hydrogen-atom transfer, as well as the problems of “hydride” transfer in chemical reactions, are discussed.
Keywords: дигідронікотинамід; квантово-хімічні розрахунки; реакційна здатність; квантово-химические расчеты; реакционная способность; dihydronicotinamide; quantum-chemical calculations; reactivity; кафедра харчової хімії